2014
DOI: 10.1111/twec.12194
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Determinants of Branch Performances in Agricultural Bank of China: A Spatial Econometric Approach

Abstract: We would like to thank the associate editor Eden Yu and two anonymous referees for helpful comments and suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They have strong purchasing power when it comes to agricultural machinery. Therefore, the level of economic development makes the largest contribution to the improvement in the AEL [21]. The basis for the operation of agricultural machinery is the land resource.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have strong purchasing power when it comes to agricultural machinery. Therefore, the level of economic development makes the largest contribution to the improvement in the AEL [21]. The basis for the operation of agricultural machinery is the land resource.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to factors such as regional economic development, land resources, as well as policy and environment, the AML in a country depends on the improvement of its AEL [7,18]. The factors affecting the AEL have also been studied in existing literature [1,[19][20][21][22]. Liu and Tian [1] found that the level of economic development is the most important factor affecting the AEL in China, followed by the scale of farmland management and the agricultural planting structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation